2020
DOI: 10.1155/2020/2037565
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Point-of-Care Testing Compared with the Standard Laboratory Diagnostic Test in the Measurement of HbA1c in Indonesian Diabetic and Nondiabetic Subjects

Abstract: Objective. This study is aimed at investigating if point-of-care testing for HbA1c (POCT-HbA1c) using the HemoCue® HbA1c 501 system could be an alternative method for diabetes screening and monitoring to replace the HbA1c measurement in a standard diagnostic laboratory. Design. This was a cross-sectional study to assess the agreement between POCT and a standard laboratory measurement method for determining the level of HbA1c. Setting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The same results were obtained by Berbudi et al, where the Bland-Altman plot analysis showed that the HbA1c by POCT and the standard laboratory method of HbA1c were within the range of agreement limits (− 1.67 to 1.3). They concluded that POCT-HbA1c is a potential method for diabetes screening and monitoring, especially when a rapid result is needed [ 36 ]. Moreover, the study by Raalten et al demonstrated high limits of agreement between the POCT HbA1c and the central laboratory HbA1c tests in non-diabetic, obese patients in the preoperative outpatient setting [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same results were obtained by Berbudi et al, where the Bland-Altman plot analysis showed that the HbA1c by POCT and the standard laboratory method of HbA1c were within the range of agreement limits (− 1.67 to 1.3). They concluded that POCT-HbA1c is a potential method for diabetes screening and monitoring, especially when a rapid result is needed [ 36 ]. Moreover, the study by Raalten et al demonstrated high limits of agreement between the POCT HbA1c and the central laboratory HbA1c tests in non-diabetic, obese patients in the preoperative outpatient setting [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classification of our participants into two age groups, young individuals (aged 0-59 years) and older adults (aged ≥60 years), revealed that there was no significant difference in HbA1c levels between these two groups. This finding suggests that HbA1c levels do not exhibit a substantial age-related variation within our study cohort [20,21]. Such uniformity in HbA1c levels across age groups may have implications for diabetes management and prevention strategies across the lifespan.…”
Section: Discussionmentioning
confidence: 63%
“…Berbudi A et al reported similar findings, revealing that the POCT-HbA1c and Lab-HbA1c were within the range of the agreement values. They came to the conclusion that POCT-HbA1c is a promising approach to screening and monitoring DM, particularly when a quick result is required [ 25 ]. Moreover, in non-diabetic obese patients, van Raalten F et al showed similar results [ 26 ].…”
Section: Discussionmentioning
confidence: 99%